Потенциал конвергентной медиа-информационной среды современной школы как пространства профессионального самоопределения - Kravtsov A. O. (Issues of Science and Education: New Approaches and Current Studies, 2024)
The article reflects the intermediate results of experimental work on the topic "Design-ing professional self-determination in a convergent and media information environ-ment. The novelty of the proposed article is determined by the fact that the authors use a convergent media and information environment as a space for professional self-determination and offer practical approaches to the implementation of the process of professional self-determination in this environment
Keywords: профессиональное самоопределение; professional self-determination; конвергентная медиа-информационная среда; convergent media and information environment